Switching porosity of stable triptycene-based cage via solution-state assembly processes. Issue 15 (3rd March 2020) - Ma, Hui; Zhai, Tian-Long; Wang, Zhen; Cheng, Guang; Tan, Bien; Zhang, Chun
Abstract : Here, a kind of triptycene-based cage is demonstrated to have good chemical stability in acid, base and boiling water. Moreover, its porosity can be tuned by varying the solution-state assembly processes. Abstract : It is a great challenge to tune the porosity of porous materials. As most porous organic cages are soluble, solution processability can be a possible way to regulate the porosity of such materials. Herein, a triptycene-based cage (TC) is demonstrated to be stable in acid, base or boiling water. Meanwhile, its porosity can be tuned by adjusting the solution-state assembly processes. TC molecules crystallized slowly from solution exhibit nearly no porosity to nitrogen (off-state). While, after rapid precipitating from methanol/dichloromethane solution, the obtained TC (TC-rp) is in a porous state and exhibit a high BET surface area of 653 m 2 g −1 (on-state).